Parricide in England and Wales (1977–2012): An exploration of offenders, victims, incidents and outcomes - Holt, Amanda (Criminology & criminal justice, 2017)
The killing of one’s parents is a neglected area in criminological scholarship, particularly in the UK, and this article presents the first national analysis of parricide in England and Wales. It draws on data from the Home Office Homicide Index to examine all recorded cases of parricide over a 36-year period and examines the characteristics of offenders, victims, incidents and court outcomes. The implications of these findings are discussed in relation to two particular dominant theoretical ideas within the field: the role of mental illness in parricide, and the notion that there are distinct forms of violence against parents that can be organized along dimensions of chronological age (i.e. juvenile/adult offender) and whether the violence is fatal (i.e. parricide) or non-fatal. The article concludes with a discussion of its wider implications for future research.